Evaluation of metals content among different cosmetic products in the Arabian market - Younes Ibrahim Md, Sahar; Abdel Maguid Md, Rania; Khaled Al-Mazroua, Maha (International Journal of Pharmacology and Toxicology, 2016)
Background: Cosmetics' use is very popular all over the world and in some parts of Arabian countries. The use of some cosmetics as Kohl is part of culture and traditions, and is used since very young ages. This makes detection of heavy metal content in cosmetics marketed in Egypt and other Arabian markets of crucial importance.Objective: To evaluate the levels of heavy metals content among different cosmetic products in the Arabian market.Methods: Different brands of; anti-freckle creams, eye shadows, eyeliners, facial powders, foundation, henna and lipsticks were purchased from open markets in Egypt and Saudi Arabia. Sample preparation and analysis was conducted, to estimate levels of twelve different metals (Pb, As, Cd, Ag, Ba, Al, Cr, Mn, Co, Ni, Cu, and Zn) using Inductively Coupled Plasma Mass Spectrometry (ICP-MS).Results: The mean concentration of some studied metals as Aluminium, lead, arsenic, copper and nickel were higher than permissible levels for cosmetics in some of the studied samples. Para- Phenylenediamine (PPD) was detected in all the studied 7 Henna samples.Conclusion: In conclusion, cosmetic contamination with metals above permissible levels is very common in most of the products available in the developing world and Arabian markets. Physicians and users must be aware of the probable toxicity of these elements and of the clinical signs of systemic poisoning. Considering popular use of cosmetics by different age groups, the hazardous cumulative effects of prolonged exposure to low concentrations of metals like; Aluminium, lead, Arsenic, nickel and copper especially in children, cannot be ruled out. Further studies are recommended in addition, cosmetic market control and legislation procedures should be thoroughly implemented.